Galatians - Esler, Philip F. (London & New York Routledge, 1998)
Paul's letter to the Galatians, sometimes known as the Magna Carta of Christian liberty, is central to the understanding of the relation of Paul and the Law and is packed with crucial historical, social and theological material. Philip F. Esler provides
Keywords: Bible. -- Galatians -- Social scientific criticism. Bible. -- Galatians -- Criticism, interpretation, etc. Intercultural communication -- Religious aspects